Análisis del impacto de la información que generan las revistas dirigidas a las mujeres profesionales entre 25 y 30 años del sector de la Alborada de la ciudad de Guayaquil - Silva Yépez, Ligia Elizabeth (2014)
The issue about professional women and the written communication media such as magazines have been discussed since the 70's with a clear intention: to promote the change of contents and message of massive media communications in a way that reflects a reality accurate to the everyday life, trajectory, personal and professional roles no just of men but of the other's population half, women. In the last decade women's organizations from different parts of the world and international agencies, had raised their voices, every time stronger than before, with the purpose of promoting the development of an image and a message that tell the diversity in women's life and their contribution to the society, in press, visual media, sound and virtual. In order to do so, they have set the necessity to have equity of gender in communication media management, and the development of its contents......